2020
DOI: 10.1002/anie.201914954
|View full text |Cite
|
Sign up to set email alerts
|

A Multidirectional Superelastic Organic Crystal by Versatile Ferroelastical Manipulation

Toshiyuki Sasaki,
Shunichi Sakamoto,
Yuichi Takasaki
et al.

Abstract: Mechanical twinning changes atomic, molecular, and crystal orientations along with directions of the anisotropic properties of the crystalline materials while maintaining single crystallinity in each domain. However, such deformability has been less studied in brittle organic crystals despite their remarkable anisotropic functions. Herein we demonstrate a direction‐dependent mechanical twinning that shows superelasticity in one direction and ferroelasticity in two other directions in a single crystal of 1,3‐bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 38 publications
4
51
0
Order By: Relevance
“…Incorporating multifarious mechanical properties in the same organic crystal is still a difficult task. [38][39][40][41] The emerging flexible organic crystals are promising optical waveguiding media and are considered to be the perfect candidates for next-generation optoelectronic devices. [42][43][44][45] Recent achievements demonstrated that elastically and plastically bendable organic crystals can be used as flexible optical media for active and/or passive light transduction.…”
Section: Manifold Mechanical Deformations Of Organic Crystals With Optical Waveguiding and Polarization Rotation Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating multifarious mechanical properties in the same organic crystal is still a difficult task. [38][39][40][41] The emerging flexible organic crystals are promising optical waveguiding media and are considered to be the perfect candidates for next-generation optoelectronic devices. [42][43][44][45] Recent achievements demonstrated that elastically and plastically bendable organic crystals can be used as flexible optical media for active and/or passive light transduction.…”
Section: Manifold Mechanical Deformations Of Organic Crystals With Optical Waveguiding and Polarization Rotation Functionsmentioning
confidence: 99%
“…Incorporating multifarious mechanical properties in the same organic crystal is still a difficult task. [ 38–41 ]…”
Section: Introductionmentioning
confidence: 99%
“…Such characteristics are reminiscent of superelasticity and ferroelasticity in shape-memory alloysin superelasticity, the daughter phase becomes unstable, and the initial mother phase reemerges upon releasing the stress, , while ferroelasticity is typically facilitated by lattice reorientation, and the structure recovers the original shape upon loading in an opposite direction . Deformable organic crystals have recently sparked vast attention in crystal engineering and pharmaceutical engineering. Nevertheless, most of those organic solids comprising simple hydrocarbon groups, albeit intriguing, are limited by their functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Designing supramolecular synthons is one of the most representative and useful approaches in crystal engineering, especially using hydrogen bonds, because of their robustness, anisotropy, and complementarity. Mechanical properties including not only elasticity and diffusion-based plasticity as a fundamental property of solids but also ferroelasticity and superelasticity ,,, as diffusion-less plastic deformation showing spontaneous strain and spontaneous shape recovery, respectively, correlate to crystal structures and can be affected by hydrogen bonds. A water molecule having flexibility in angles and length of its hydrogen bonds and the ability of bond recombination , in the crystalline state can be a possible tool for crystal design.…”
Section: Introductionmentioning
confidence: 99%